A General Solution Framework for Component-Commonality Problems - Nils Boysen; Armin Scholl (BuR - Business Research, 2009)
Component commonality - the use of the same version of a component across multiple products - is being increasingly considered as a promising way to offer high external variety while retaining low internal variety in operations. However, increasing commonality has both positive and negative cost effects, so that optimization approaches are required to identify an optimal commonality level. As components influence to a greater or lesser extent nearly every process step along the supply chain, it is not surprising that a multitude of diverging commonality problems is being investigated in literature, each of which are developing a specific algorithm designed for the respective commonality problem being considered. The paper on hand aims at a general framework which is flexible and efficient enough to be applied to a wide range of commonality problems. Such a procedure based on a two-stage graph approach is presented and tested. Finally, flexibility of the procedure is shown by customizing the framework to account for different types of commonality problems.
urn:nbn:de:0009-20-19422
Keywords: 650; component-commonality; graph approach; optimization; product variety; Produktdifferenzierung; Modularisierung; Kosten-Nutzen-Analyse; Mathematische Optimierung; Graphentheorie; Theorie